Clinical role of fluorescence imaging in colorectal surgery - an updated review. (1st December 2020) - Ghuman, Amandeep; Kavalukas, Sandra; Sharp, Stephen P.; Wexner, Steven D.
ABSTRACT: Introduction: Colorectal surgery has markedly advanced due to the introduction of laparoscopic and robotic surgery. During the past 20 years, these two modalities have been further enhanced by fluorescence imaging. Areas covered: This article will review the common and novel uses for fluorophores in colorectal surgery, including tissue perfusion for anastomotic creation, ureter identification, lymphatic mapping, and tumor localization. Expert opinion: The versatility of this technology permeates through many aspects of colorectal procedures. The white light spectrum has historically been the only available modality to visualize tissue perfusion, tumor implants, and structures including the ureters and lymph nodes. The ability of the near-infrared spectrum to penetrate biologic tissues allows the identification of these structures with injection of fluorophores. The two most common intravenously utilized fluorophores are methylene blue and indocyanine green. Additionally, novel tumor marker-specific fluorophores are being investigated for purposes of cancer detection.